Efficacy of tadalafil for the treatment of erectile dysfunction at 24 and 36 hours after dosing: a randomized controlled trial - Porst, Hartmut; Padma-Nathan, Harin; Giuliano, François; Anglin, Greg; Varanese, Lucio; Rosen, Raymond (Urology (Ridgewood, N.J.), 2003)
To examine the therapeutic effects of tadalafil on erectile dysfunction (ED) at 24 and 36 hours after dosing. A multicenter, randomized, double-blind, placebo-controlled, parallel-group study of 348 men (mean age 57 years) with ED was conducted in Europe and the United States. Patients were stratified by baseline severity of ED using the Erectile Function domain score of the International Index of Erectile Function and then randomly allocated within the severity group to receive tadalafil 20 mg (n = 175) or placebo (n = 173). Subsequently, participants were randomly assigned to two 4-week treatment intervals, during which they were requested to attempt sexual intercourse approximately 24 or 36 hours after tadalafil or placebo dosing. The primary outcome measure was the proportion of successful sexual intercourse attempts (completed to ejaculation) according to patient self-report using the Sexual Encounter Profile diary. Of the 348 patients, 327 (94%) completed the trial (163 of 175 in the tadalafil group and 164 of 173 in the placebo group). Thirty-six hours after tadalafil dosing, 59.2% of intercourse attempts were successful versus 28.3% in the placebo group ( P <0.001). The proportion of successful intercourse attempts at approximately 24 hours after treatment was also significantly greater with tadalafil (52.9%) than with placebo (29.1%; P <0.001). Tadalafil was well tolerated. The incidences of four treatment-emergent adverse events were significantly greater in the tadalafil group than in the placebo group (all P <0.05): headache, flushing, dyspepsia, and myalgia. Tadalafil 20 mg is an effective and well-tolerated treatment for ED that has a period of responsiveness of up to 36 hours.